The Evolving Role of FDG-PET/CT in the Diagnosis, Staging, and Treatment of Breast Cancer - Paydary, Koosha; Seraj, Siavash Mehdizadeh; Zadeh, Mahdi Zirakchian; Emamzadehfard, Sahra; Shamchi, Sara Pourhassan; Gholami, Saeid; Werner, Thomas J.; Alavi, Abass (Molecular imaging and biology, 2019)
The applications of 2-deoxy-2-[ 18 F]fluoro- d -glucose positron emission tomography/X-ray computed tomography (PET/CT) in the management of patients with breast cancer have been extensively studied. According to these studies, PET/CT is not routinely performed for the diagnosis of primary breast cancer, although PET/CT in specific subtypes of breast cancer correlates with histopathologic features of the primary tumor. PET/CT can detect metastases to mediastinal, axial, and internal mammary nodes, but it cannot replace the sentinel node biopsy. In detection of distant metastases, this imaging tool may have a better accuracy in detecting lytic bone metastases compared to bone scintigraphy. Thus, PET/CT is recommended when advanced-stage disease is suspected, and conventional modalities are inconclusive. Also, PET/CT has a high sensitivity and specificity to detect loco-regional recurrence and is recommended in asymptomatic patients with rising tumor markers. Numerous studies support the future role of PET/CT in prediction of response to neoadjuvant chemotherapy (NAC). PET/CT has a higher diagnostic value for prognostic risk stratification in comparison with conventional modalities. With the continuing research on the treatment planning and evaluation of patients with breast cancer, the role of PET/CT can be further extended.